Unlimited Discretion, Eroded Certainty: Reformulating Criminalization of Narcotics Crime in Indonesia - Arianti, Nofalinda; Maryano, Maryano; Rattanapun , Supot (Journal Evidence Of Law, 2025)
Sentencing in narcotics crime cases in Indonesia remains problematic, particularly concerning legal certainty. The striking disparity in court decisions—despite similar legal facts—reflects the absence of standardized sentencing parameters. Furthermore, the wide scope of judicial discretion without objective guidelines increases the risk of injustice in criminal adjudication. This study aims to examine the realization of legal certainty in narcotics sentencing, analyze the role and limits of judicial discretion, and formulate the need for sentencing reform in Indonesia. Using a normative and empirical legal approach, the study analyzes 25 court verdicts and is supported by interviews with legal practitioners. The findings reveal that disparity and unregulated discretion contribute to systemic uncertainty in sentencing practices. Therefore, comprehensive reform is necessary, including binding sentencing guidelines, restricted judicial discretion, and strengthened rehabilitative approaches. This research contributes to the formulation of progressive criminal law reforms based on justice, proportionality, and predictability.